Preventing Foodborne Illness: E. coli O157:H7 - Keith R. Schneider; Renée M. Goodrich Schneider; Michael A. Hubbard; Alexandra Chang (EDIS)
Revised! FSHN-03-1, a 5-page fact sheet by Keith R. Schneider, Renée Goodrich Schneider, Michael A. Hubbard, and Alexandra Chang, discusses the common foodborne pathogen E. coli O157:H7, especially as it concerns food handlers, processors, and retailers. Includes references. Published by the UF Department of Food Science and Human Nutrition, November 2009.